Peran Sustainability Report dalam Memperkenalkan Prinsip ESG pada Tata Kelola Perusahaan - Tiara Maulida Kharisma Dwi Cahya (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Sustainability reports play an important role in introducing Environmental, Social, and Governance (ESG) principles into corporate governance by providing transparent information on sustainability performance covering environmental, social, and ethical governance aspects. This study uses a qualitative approach with literature studies, official reports, and company documentation as the main data sources, without using field or quantitative methods. The results show that sustainability reports can enhance a company's reputation, strengthen internal accountability, and build stakeholder trust, while also serving as a strategic tool in ESG-based decision-making. The data presented in the report enables the evaluation of long-term impacts, the identification of areas for improvement, and the strengthening of a sustainable corporate culture. In addition, sustainability reports encourage industry recognition and awards, which enhance a company's credibility in the public eye. With consistent and systematic publication, sustainability reports become an effective instrument for integrating ESG principles into corporate management strategies, ensuring long-term sustainability, and building effective communication with all stakeholders.